PO-03 - Khorana score and histotype predict the incidence of early venous thromboembolism (VTE) in Non Hodgkin Lymphoma (NHL). A pooled data analysis of twelve clinical trials of Fondazione Italiana Linfomi (FIL). Issue 140 (April 2016) - Santi, R.M.; Ceccarelli, M.; Catania, G.; Monagheddu, C.; Evangelista, A.; Bernocco, E.; Monaco, F.; Federico, M.; Vitolo, U.; Cortelazzo, S.; Cabras, M.G.; Spina, M.; et al.
Abstract : Background: Recent studies show that the risk of VTE in NHL pts is similar to that observed in high risk solid tumors (i.e. pancreatic, ovarian cancer). VTE in NHL occurs in most cases within three months from diagnosis and can have substantial impact on treatment delivery and outcome as well as on quality of life. However few data are available on potential predictors. Aims: To better clarify the epidemiology of early (within six months from treatment start) VTE in NHL we conducted a pooled data analysis of 12 clinical trials from FIL. Our analysis included basic demographic features, lymphoma-related characteristics as well the Khorana score (based on histology, BMI, platelets WBC and HB counts) which is extensively used in solid tumors to predict VTE risk. Patients and methods: From Jan. 2010 to Dec. 2014, all pts with B-cell NHL enrolled in prospective clinical trials from FIL for frontline treatment were included. For 9 studies study period included the entire trial population was included. The analyses were conducted based on CRFs as well as pharmacovigilance reports. VTE definition and grading was stated according to standard criteria of toxicity (CTCAE V4.0). Cumulative incidence of VTE from the study enrollment was estimated using the method described by Gooley et al. accounting for death from any causes as a competing risk. The Fine & Gray survival model was used to identify predictors of VTE among NHL pts. Factors predicting the grade of VTE were investigated using an ordinal logistic regression model. This pooled data analysis was approved by local IRB. Results: Overall, 1, 717 patients belonging to 12 studies were evaluated. Eight were phase I/II or II (25% of pts) and 4 phase III (75% of pts). M/F ratio was 1.41, Median age was 57, (IQ range (IQR) 49-66). Histologies were: DLCL-B 34%, FL 41%, MCL 18%, other 6%. Median BMI was 25 (IQR 22-28). Median Hb, WBC and platelets counts were 13g/dl) (IQR 11.5-14.2), 7.1*10^ 9 /l (IQR 5.6-10.3), 224*10^ 9 /l (IQR 169-298), respectively. 1189 pts were evaluable Khorana score: 58% low risk, 30% intermediate risk, 12% were high risk. Human erythropoetin support was given to 9% of patients. All pts received Rituximab. Planned therapeutic programs included ASCT in 27% of pts, conventional chemotherapy in 67% a conventional chemotherapy plus lenalidomide in 6%. Overall 59 any grade VTE episodes occurred in 51 pts (2.9%), including 21 grade III-IV VTE (18 pts). None was fatal. Median time from study enrolment to VTE was 63 days (IQR: 35-110). Considering death as a competitive event the 6 months cumulative incidence of VTE was 2, 2% in low risk Khorana score, 4.5% (95%IC: 2.3-6.7) in intermediate and 6.6% (95%IC: 2.4-10.8) in high risk (p = 0.012) (figure 1). Khorana score was predictive also for grade III-IV events as they were 0, 7% (95% CI:0.1-1.4) in low risk and 2.0% (95% CI:0.8-3.3) in intermediate-high risk (p = 0.048). The results were similar also after excluding lenalidomide containing studies. The Fine and Gray multivariate analyses, adjusted for age and stage, showed that Khorana score (intermediate risk adjHR = 1.96; 95%IC: 0.84-4.56 and high risk adjHR = 3.81; 95%IC: 1.51-9.58) and DLCL-B histotype (adjHR = 2.58; 95% CI: 1.01-6.55) were independently associated to an increased risk of VTE. Moreover an ordinal logistical regression model indicated that the increase of one point in the Khorana score resulted in an increased risk of VTE (OR = 1.85; 95% CI: 1.23-2.79). Fig. 1 Conclusions: Our results suggest that DLCL-B histotype and Khorana score are predictors of VTE in NHL. The latter might become a simple and effective tool to assess the risk of VTE in NHL. Prospective validation including also patients not eligible for clinical trials is needed.